Analysis of Classroom Management Skills of Prospective Vocational Teachers during Teaching Practice in DKI Jakarta - Pamungkas, Brahmansyah Rajif; Iriani, Tuti; Ramadhan, M. Agphin (Indonesian Journal of Education and Mathematical Science, 2025)
This study examined the classroom management skills of prospective vocational teachers in the Building Construction Expretise Program during teaching practice in DKI Jakarta. Participants were 17 prospective teachers and 286 students, selected through purposive sampling. The study used a mixed-methods sequential explanatory design, combining quantitative data from a Likert-scale questionnaire and qualitative data from classroom observations. The prospective vocational teachers showed strong skills in creating a positive classroom environment (76.2%) and preventing problems (72.0%). However, they had dificulties in managing existing problems (53.4%) and in building effective classroom systems (46.0%). Weak areas included enthusiasm for teaching, giving praise and criticism, giving rewards and punishments, coaching, managing mobile phone, classroom design, motivating students, and building relationships. These findings indicate that prospective vocational teachers need more training and examples to improve their classroom management skills.